Time in the domestic space: Reflections during a pandemic - Fernández Villalobos, Nieves (Universidad ORT Uruguay, 2021)
Different disciplines, based on various assumptions, focus their attention on a variety of layers of time. In relation to architecture, time can be considered from different meanings and the way in which we link it to spaces. We usually talk about Physical Time, it is astronomical, mathematical, and quantitative. But there is also Ontological Time, psychic and lived. Emotional Time is eminently subjective, variable, unstable and qualitative, and we can define Mental Time as abstract and intellectual. The House is a fundamental instrument for living. It must provide us with shelter and security, accommodate our memory and allow our dreams; It must be flexible to incorporate various improvised functions, enable our privacy and happy coexistence with those we live in; it must keep us alert to the subtle changes in our environment; in short, it must contain different layers and manifestations of time. The situation experienced during the pandemic may suggest new forms of living space, different from the ones we were used to. We have all experienced how our perception of time has changed at this stage, and how the house has been adapted, out of necessity, to include functions that were usually performed outside of it. Space is the raw material to create an architectural experience, and if we add time as an extra dimension, space becomes dynamic. Concepts such as change, growth, evolution, adaptability, memory and interaction must come into play in our projects. Reflection on time and its different meanings through various examples from the world of art, architecture, and design, can help us to create kinder, dynamic and flexible domestic spaces, that can easily adapt to new circumstances.